Studi Keakuratan Pengukuran Getaran Mikro (Studi Kasus Gedung Juo Chiun dan Rumah Sakit NCKUdi Taiwan) - Irda Yunita Irda Yunita (Jurnal Serambi Engineering, 2016)
Traffic-induced building vibrationis a major environmental problem, specifically forbuilding hospital and high-tech industries building, since it may result in structural damage and malfunctioning of sensitive equipment. The Juo Chiun Building and NCKU Hospital are the example of buildings in Taiwan that its location adjacent to the highway and are susceptible to vibrations due to traffic load. The experimental measurements can be performed to determine the traffic-induced vibrations in buildings. This journalfocuses on the investigation of the accuracy of the experimental instruments for the measurement of micro vibration, especially the micro vibration induced by road traffic. The measurement at two different buildingsconducts by usingdifferent voltages and sampling rates, then the results will be illustrated, analyzed visually, and compared in this journal in order to ensure the accuracy.Moreover, the maximum dB-frequency diagram obtained from field experiment will be studied. The maximum dB-frequency diagram results will be compared with the table of vibration guideline to indicate the appropriateness of the building as VC-A standard in semi-conductor industries building